Analisis Dimensi Kualitas Pelayanan Televisi Berlangganan - Rorio Gomgom Simarmata (Universitas Mercu Buana, 2019)
Broadcasting technology in a telecommunication company (TV) on continues to evolve along with the development of information and communication technology (ICT). Today's technological developments have grown rapidly and become more complex. The companies that do not bring innovation and the differentiation of their products will be left out of competitors in the same field. Users are exposed to a variety of products on the market that they may choose. How a company can grow in the midst of market competition depends on its ability to satisfy its customers. This study aims to analyze the achievements of pay TV companies in Indonesia from the point of view of customers, which is from satisfaction with product quality and quality of service. Importance-Performance Analysis (IPA) is conducted to determine the status of indicators related to product and service quality to provide input to management in taking strategic steps. The results reveal that enhancement priorities are attractive design properties, following the latest trends, Resistance to intervention factors (weather), Variations in the channel given, The employee's progress in the repair visit, The employee’s speed in responding to request customer.